Lenalidomide Augments Differentiation of Cultured Hair Follicle Derived Melanocyte Stem Cells Into Functional Melanocytes - Uma Kumari; Naveed Pervaiz; Harjot Kaur; Himani Sharma; Davinder Parsad; Ravinder Kumar (Dermatology Practical & Conceptual, 2023)
Introducion: Melanocyte progenitors are embryonically derived from the neural crest and subsequently get localized in hair follicles and epidermis to provide hair and skin pigmentation. These progenitor cells in hair follicles repeatedly proliferate and differentiate to maintain pigmentation. Vitiligo, a pigmentary disorder, is associated with loss of melanocytes. Repigmentation of vitiligo lesions mainly depends upon the proliferation, migration and differentiation of melanocyte stem cells (MelSCs) into functional melanocytes. Current study is designed to check the efficacy of lenalidomide, an imide drug in the differentiation of MelSCs into functional melanocytes.